When to Suspect DRUJ's Instability in Children? Case Report of a Rare Presentation of Distal Forearm Fractures - Saugy, Claire-Anne; Bregou, Aline Bourgeois (European Journal of Pediatric Surgery Reports, 2022)
Pediatric displaced distal metaphyseal ulnar fractures and distal radial buckle fractures are common. However, to the best of our knowledge, their association has never been specifically reported. Thus, classification and management of this pattern remain challenging especially in young children. Distal radioulnar joint (DRUJ)'s assessment is difficult. A Galeazzi-equivalent injury should be suspected. We report the case of a 2-year-old boy who presented the above-mentioned association of forearm fractures and compare our management with actual recommendations. We would recommend a low-suspicion threshold for DRUJ's instability in young children presenting with displaced distal metaphyseal ulnar fracture associated with distal radial buckle fracture. That suspicion should raise the necessity of appropriate treatment and follow-up.
Keywords: Forearm fracture; Children; distal radioulnar joint; Galeazzi-equivalent injury